Nexus between intellectual capital and business performance: evidence from India - Faizi Weqar; Zubair Ahmad Sofi; S.M. Imamul Haque (Emerald Publishing Limited, 2020)
The prime intention of this study is to examine the influence of intellectual capital (IC) on the financial performance of Indian companies listed on Standard and Poor Bombay Stock Exchange Sensitive Index (BSE SENSEX).The study employs the data of 30 most significant and most prominent companies of India listed on BSE SENSEX for 10 years from 2009–2010 to 2018–2019. Value Added Intellectual Coefficient (VAICTM) methodology developed by Pulic (2000) was employed for measuring the efficiency of the IC.The efficiency of IC is substantially and positively associated with the financial performance of the Indian companies as measured by return on assets (ROA), market-to-book (MB) ratio and return on equity (ROE). Amongst the three dimensions of VAIC, capital employed efficiency (CEE) was the most vital element in contributing to the firm financial performance, followed by human capital efficiency (HCE). Structural capital efficiency (SCE) only helps in enhancing the ROA of Indian firms.The study results are only restricted to the 30 companies of India listed on S&P BSE SENSEX Index. Thus generalization of the result needs especial caution.The study fills the void in the current literature of IC and business performance and extends the understanding of their relationship by providing empirical evidence.